2023
DOI: 10.1186/s13018-023-03692-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparable clinical outcomes of culture-negative and culture-positive periprosthetic joint infections: a systematic review and meta-analysis

Abstract: Purpose The aim of this study was to compare the clinical outcomes of culture-negative periprosthetic joint infection (CN PJI) with those of culture-positive periprosthetic joint infection (CP PJI). Methods Data were obtained from Embase, Web of Science and EBSCO for all available studies comparing the clinical outcomes of CN PJI with those of CP PJI. The quality of the studies was scored using the Newcastle–Ottawa scale (NOS). Pooled odds ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
4
0
3
Order By: Relevance
“…В 2018 г. опубликованы данные систематического мета-анализа исходов лечения КНИ, который включал обзор 8 англоязычных статей [30]. По объединенным данным, частота встречаемости инфекции с отрицательным микробиологическим посевом составила 11 % (n = 504) с частотой успеха 85-95 %, не было различий в частоте успеха с КПИ.…”
Section: оригинальные статьиunclassified
See 2 more Smart Citations
“…В 2018 г. опубликованы данные систематического мета-анализа исходов лечения КНИ, который включал обзор 8 англоязычных статей [30]. По объединенным данным, частота встречаемости инфекции с отрицательным микробиологическим посевом составила 11 % (n = 504) с частотой успеха 85-95 %, не было различий в частоте успеха с КПИ.…”
Section: оригинальные статьиunclassified
“…По объединенным данным, частота встречаемости инфекции с отрицательным микробиологическим посевом составила 11 % (n = 504) с частотой успеха 85-95 %, не было различий в частоте успеха с КПИ. Результаты недавнего мета-анализа, в который было включено 30 исследований, демонстрируют аналогичную или лучшую эффективность лечения КНИ в сравнении группой культуропозитивной ППИ -соответственно 81 и 76,4 % [30]. Одной их вероятных причин успеха лечения КНИ может быть банальное отсутствие инфекции в протезированном суставе, другой -наличие низковирулентных микроорганизмов, которые легче лечить, чем высоковирулентные, такие как метициллин-резистентный золотистый стафилококк [6].…”
Section: оригинальные статьиunclassified
See 1 more Smart Citation
“…Research studies regarding outcomes following CN PJI have demonstrated differing results. Some scholars state that CN PJI yields worse outcomes as compared to those of culture positive (CP) PJI patients, arguing that the lack of identification of an infecting organism obscures treatment options and complicates both diagnosis and management of the infection (F. Li et al, 2023;Mortazavi et al, 2011). Others, however, have demonstrated that outcomes are more comparable or are even favorable for patients with CN PJI, attributing the negative culture to be indicative of a less severe infection (F. Li et al, 2023;H.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative microbiological diagnosis is the main condition of treatment in patients with PJI who are planned to undergo one-stage septic exchange [10], whereas two-stage revision is recommended for patients with culture-negative PJI [11].…”
Section: Introductionmentioning
confidence: 99%